Analysis of Differently Shaped Footing for A Midrise Structure Considering Lateral Forces Using SAFE Software : A Review - Vijay Singh Dasoondi; Rahul Sathbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
In this study, comparative analysis was done on three different footing namely Single Footing, Combined Footing and MAT or Raft Footing with similar loading conditions. This included comparative study of their structural behaviour considering for building frame G+5. A comparison in analysis results was done on certain important parameters such as deflection, support reaction, axial force, torsion and Shear force. The cost analysis was conducted in this experimental investigation as per S.O.R, In this paper we are reviewing the literatures and publications related to analysis of footing and soil structure interaction.